Measurements of radon emanation from soil samples in triple-junction of North and East Anatolian active faults systems in Turkey - Baykara, O; Dogru, M; Inceöz, M; Aksoy, E (Pergamon-Elsevier Science Ltd, 2005)
Using the closed-can technique, radon exhalation rate, radon concentration and effective radium content have been carried out for soil samples collected from triple-junction of the North Anatolian Fault System and East Anatolian Fault System. The measured maximum values of the exhalation rate and radon concentration in the system were 400.7 (mBqm(-2)h(-1)) and 8.10 Bqkg(-1), respectively. However, effective radium concentration in soil samples has been found to vary from 0.02 to 0.80 Bq kg(-1). Linear correlation was observed between soil-gas radon concentration, effective radium content and radon exhalation rate. The linear correlation coefficient between radium content and radon concentration was found to be 0.91. Nevertheless, it was found that there is a linear correlation (R-2 = 0.99) between the radon concentration and exhalation rate. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: radon emanation; soil radon; CR-39; closed-can technique